Epigenetic Mechanisms in the Control System of the Kidney Function in Norm - Dolomatov, Sergey; Zukow, Walery (Journal of Education, Health and Sport, 2019)
The publication is devoted to the consideration of the mechanisms of the adaptive capabilities of the kidney in norm, based on epigenetic control systems of protein biosynthesis. This paper emphasizes the high plasticity of epigenetic mechanisms. The thesis that the epigenetic mechanisms have a high degree of plasticity and perform an important function in adaptive reactions of the kidney, is illustrated by data on the epigenetic transformation of key proteins of various nephron sections. In addition, brief information is given on the possible involvement of epigenetic mechanisms in adaptive rearrangements of arginine vasopressin and natriuretic peptides. High plasticity, accuracy and power of epigenetic systems regulating the adaptive capabilities of the kidney are emphasized.